Optimization of the Decolorization of the Reactive Black 5 by a Laccase-like Active Cell-Free Supernatant from Coriolopsis gallica - Amal Ben Ayed; Bilel Hadrich; Giuliano Sciara; Anne Lomascolo; Emmanuel Bertrand; Craig B. Faulds; Héla Zouari-Mechichi; Eric Record; Tahar Mechichi (Microorganisms, 2022)
The textile industry generates huge volumes of colored wastewater that require multiple treatments to remove persistent toxic and carcinogenic dyes. Here we studied the decolorization of a recalcitrant azo dye, Reactive Black 5, using laccase-like active cell-free supernatant from Coriolopsis gallica. Decolorization was optimized in a 1 mL reaction mixture using the response surface methodology (RSM) to test the influence of five variables, i.e., laccase-like activity, dye concentration, redox mediator (HBT) concentration, pH, and temperature, on dye decolorization. Statistical tests were used to determine regression coefficients and the quality of the models used, as well as significant factors and/or factor interactions. Maximum decolorization was achieved at 120 min (82 ± 0.6%) with the optimized protocol, i.e., laccase-like activity at 0.5 U mL−1, dye at 25 mg L−1, HBT at 4.5 mM, pH at 4.2 and temperature at 55 °C. The model proved significant (ANOVA test with p < 0.001): coefficient of determination (R²) was 89.78%, adjusted coefficient of determination (R²A) was 87.85%, and root mean square error (RMSE) was 10.48%. The reaction conditions yielding maximum decolorization were tested in a larger volume of 500 mL reaction mixture. Under these conditions, the decolorization rate reached 77.6 ± 0.4%, which was in good agreement with the value found on the 1 mL scale. RB5 decolorization was further evaluated using the UV-visible spectra of the treated and untreated dyes.